Interim report on mepsir project (Measuring European Public Sector Information Resources). State: Portugal - Jacquinet, Marc (2006)
This document holds the interim results of the MEPSIR research project in Portugal. It describes activities carried out and results achieved from April 2005 to December 2005 for the evaluation of EU Directive n.º 2003/98/EC of 17 November 2003.